PEAC Events: identification of Predictable, Expensive, Avoidable, and Cardinal events within a learning health system. (2017) - Whyatt, David; Yap, Matthew; Tuson, Matthew; Kok, Mei Ruu; Turlach, Berwin; Boruff, Bryan; Geelhoed, Elizabeth; Vickery, Alistair
No abstract available